Penelitian Tentang Strategi Dan Inovasi Dalam Program Kegiatan Untuk Mempercepat Pemulihan Sektor Ekonomi - Joko Yuwono; Nur Isnaini (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to investigate the strategies and innovations contained in activity programs designed to accelerate the recovery of the economic sector. In this context, a detailed analysis was carried out of the various strategies implemented and the innovations used in an effort to improve performance and restore the affected economic sectors. The research methods used include literature studies, primary data analysis, and a review of existing best practices. It is hoped that the results of this research will provide deeper insight into the role of strategy and innovation in achieving sustainable economic recovery.